Economic losses due to low coverage of lipid-lowering therapy in patients with cardiovascular diseases in the Russian Federation - Yu. A. Balanova; A. V. Kontsevaya; A. E. Imaeva; O. I. Karpov; M. B. Khudyakov (Рациональная фармакотерапия в кардиологии)
Aim. To assess the economic burden associated with the absence of lipid-lowering therapy (LLT) in patients with cardiovascular diseases (CVD) and hypercholesterolemia (HCS) in the Russian population in 2016, including direct costs of the health care system  and indirect economic losses due to premature death, absenteeism and disability.Material and methods. The calculation includes data  from local population-based studies (prevalence of HCS, treatment coverage and efficiency), as well as Russian statistics on CVD for 2016. Population attributive risk (PAR) was determined, which reflected the incidence of excessive morbidity associated with the lack of HCS therapy in developing CVD for the Russian population, based  on LDL cholesterol level. Direct and indirect components of economic burden associated with the absence of LLT have been calculated, as well as the number of deaths with the calculation of "lost years of potential life" lacking to reach the age of 72 years, and losses associated with premature mortality in the economically active age. Indirect costs (economic losses) included non-received gross domestic product (GDP) due to premature mortality and disability in economically active age and loss of earnings due to temporary disability (TD). To estimate the indirect costs,  the number of people of the working age  with permanent disability in each  of the disability groups  has  been  calculated. The indirect costs  due  to temporary disability were  calculated as payments of salary including for days  of incapacity for work multiplied by the number of days of TD according the Russian statistics data.Results. The absence of LLT  in people with HCS increases the  risk of CVD related mortality by one  third, death due  to cerebrovascular diseases, including stroke,  by more than a half. PAR was estimated to be 17% for CVD mortality in general, 26% for cerebrovascular diseases. Contribution of HCS and  the  lack of LLT to morbidity is 29% for ischemic heart  disease (IHD), 20% for myocardial infarction. Outpatient calls take  the  first place among all out-patient care statistics, and those  associated with IHD are in the leading position among them.  Hospitalization takes the second  place. The absence of LLT caused  the loss of more than 400,000 years of life in economically active age. The direct costs are determined by expenses for hospitalizations in the presence of IHD. The share of direct costs for hospitalizations is 86%, while in the presence of cerebrovascular diseases it is 76.8%. Payments for disability allowance, which refers to direct non-medical costs, exceed 154 million Russian rubles (RUR) for IHD and 104 million RUR for cerebrovascular diseases. The biggest share  of economic burden associated with the lack of LLT in individuals with this risk factor  is accounted for indirect economic losses: about 507 billion RUR in IHD, of which more  than  90  billion RUR are  associated with myocardial infarction. The costs associated with cerebrovascular diseases make up over 305 billion RUR, the vast majority of which is due to stroke: over 248 billion RUR. Due to the low LLT coverage in the Russian Federation, the economic burden associated with its absence is over 80% of the calculated HCS related losses in total. Conclusion. Economic burden of the lack of LLT in HCS patients is calculated as 530 billion RUR, which is about 0.6% of GDP in 2016, and the largest part of expenditures is related to IHD. The increased awareness of HCS and its improved control with increasing treatment coverage will make possible to lower cholesterol values at the population level, which will also reduce  the economic burden of this risk factor for CVD.